2020
DOI: 10.1038/s41467-020-18313-y
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor signalling in macrophages promotes TREM-1-mediated prostate cancer cell line migration and invasion

Abstract: The androgen receptor (AR) is the master regulator of prostate cancer (PCa) development, and inhibition of AR signalling is the most effective PCa treatment. AR is expressed in PCa cells and also in the PCa-associated stroma, including infiltrating macrophages. Macrophages have a decisive function in PCa initiation and progression, but the role of AR in macrophages remains largely unexplored. Here, we show that AR signalling in the macrophage-like THP-1 cell line supports PCa cell line migration and invasion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 64 publications
2
69
0
Order By: Relevance
“…The TME and immune-related biomarkers play essential roles in the precise treatment of some cancers [22]. The TME, including immune cells, stromal cells, and cytokines, has been proven to determine the biological behavior of cancer cells [23][24][25]. Infiltrating immune and stromal cells account for the majority of normal cells in solid tumor tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The TME and immune-related biomarkers play essential roles in the precise treatment of some cancers [22]. The TME, including immune cells, stromal cells, and cytokines, has been proven to determine the biological behavior of cancer cells [23][24][25]. Infiltrating immune and stromal cells account for the majority of normal cells in solid tumor tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The contributing role(s) of the androgen receptor in BPH is not fully understood, and the involvement of androgen receptor signaling in prostatic inflammation may contribute to this complexity (48,49). Reduced circulating androgen levels in aging men might contribute to .…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive function of androgens has been reported in numerous studies ( 32 ). The contributing role(s) of the androgen receptor in BPH is not fully understood, and the involvement of androgen receptor signaling in prostatic inflammation may contribute to this complexity ( 48, 49 ). Reduced circulating androgen levels in aging men might contribute to increased inflammation in BPH, but whether the increase in inflammation is in response to a stimulus (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, signaling via TREM-1 is significantly related to the development and progression of chronic lymphocytic leukemia ( 15 ). TREM-1 is induced in macrophages by the androgen receptor signaling pathway in prostate cancer, and increases the motility and invasive capacity of prostate cancer cells ( 16 ). In recent years, many studies have suggested various strategies for regulating TREM-1 expression and activity to block the interaction between TREM-1 and its ligands to treat a number of diseases, including cancer ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%